THE EFFECT OF BALANCED SCORECARD IMPLEMENTATION ON THE PERFORMANCE OF COOPERATIVE AND LABOR SERVICE OF BOYOLALI REGENCY - Harena Susianti; Setyani SH; Yuniatin Trisnawati DKW (ADVANCE, 2018)
The objective of this research is to provide empirical evidence that Financial Perspective, Customer Perspective, Internal Business Process Perspective and Learning and Growth Perspective have a significant influence on the performance of Boyolali District Cooperative and Labor Office. Population in this research is Employee of Department of Cooperation and Labor in Boyolali District. Based on these criteria and the results of questionnaires distribution, the number of samples obtained in this study were 46 people. Analytical techniques in this study consisted of, testing the quality of the questionnaire, the classical assumption test, multiple linear regression analysis, t test. Test F and coefficient of determinas. The results of this study proves that the financial perspective has an insignificant effect on the performance of Boyolali District Cooperative and Labor Office, the customer perspective has a significant positive effect on the performance of the Cooperative and Labor Office of Boyolali Regency, internal business process perspective has a significant effect on the Dinas performance, but the relationship is negative, and learning and growth perspective has a positive and significant effect on the performance of Boyolali District Cooperative and Labor Office. From these results the most dominant influential is the perspective of learning and growth. The result of R2 test shows that the percentage of influence given by variable of financial perspective, customer perspective, internal business process perspective, and learning and growth perspective on employee performance of Boyolali District Cooperative and Labor Office is 0,848 or 84,8% while the rest equal to 15,4 % influenced by other variables not used in this studyKeywords: Financial Perspective, Customer Perspective, Internal Business Process Perspective, Learning and Growth Perspective, Service Performance